Effect of Pneumatic Balloon Dilation to The Changes of Eckardt Score in Patient With Achalasia - Budi Widodo; Iswan Abbas Nusi; Titong Sugihartono (Biomolecular and Health Science Journal, 2020)
Introduction: Achalasia is an esophageal motility disorder, but its pathogenesis remains unclear. The highest incidence is among adults aged 30 – 60 years with the prevalence of 10/100.000 population. Diagnosis of achalasia is based on symptoms and upper endoscopy, barium esophagogram, and esophageal manometry. Pneumatic Balloon Dilation (PBD) is one of the treatment options, whether it is fluoroscopy-guided or direct endoscopy guided. This study aims to analyze the effect of PBD on the changes of Eckardt score among achalasia patients.Methods: An analytical observational study with a retrospective and prospective design was conducted on 18 achalasia patients who performed PBD at Dr. Soetomo General Hospital. Data were then analyzed using t-test. Results: The mean age was 47.8±12.5 years, and the mean achalasia duration was 18.3±5.9 months. There were no differences of achalasia cases between men and women. The mean body weight in the pre and post PBD was 50.9±6.2 vs 53.1±6.5 kg with delta 2.19±1.88 (p <0.0001). The mean BMI in the pre and post PBD was 20.2±2.2 vs 21.1±2.5 kb/m2 with delta 0.89±0.78 (p <0.0001). In addition, the mean Eckardt score in the pre and post PBD was 10.17±1.47 vs 2.5±0.86 (p <0.0001). There were 3 patients with Eckardt score of 4 after PBD and no weight loss after one-month evaluation. Conclusion: There was a significant difference of Eckardt score before and after PBD. The improvement of the Eckardt scores led to the change of weight and body mass index among achalasia patients.